An analysis of ramie fiber (Boehmeria nivea L. Gaud) treated with low temperature plasma using a mathematical model - Markus Paramahasti; Valentinus Galih Vidia Putra; Yusril Yusuf (Arab Journal of Basic and Applied Sciences)
This research aims to characterize low-temperature plasma-treated ramie fibers (Boehmeria nivea L. Gaud), create a mathematical model, and analyze them using image processing. The effects of low-temperature plasma treatment on ramie fibers were investigated using 30 kV output powers, 4-min treatment times, and a 4 cm electrode distance. SEM and FT-IR spectroscopy were used to investigate various aspects of the ramie fiber’s chemical properties and surface topography. This study used a statistical approach to analyze the SEM images. The statistical analysis was used to investigate the surface roughness using the SEM images. FT-IR analysis discovered that fibers that were exposed for four minutes differed from untreated fibers. According to the findings, plasma treatment caused: (1) ramie fiber became more hydrophilic, as indicated by the presence of hydrophilic functional groups such as hydroxyl (O–H), carboxyl (O–C), and carbonyl (C=O) in FT-IR with a deeper T%, (2) ramie fiber mass reduction was accompanied by an increase in surface roughness via SEM testing and image processing, and (3) plasma-treated fiber had a coefficient of mass variation (CV) of 0.7211 higher than untreated fiber. The novelty of this study is the use of image processing in SEM to observe surface roughness and its relationship to the chemical structure of ramie fibers observed with FT-IR. Another novelty of this research is the mathematical model of the interaction of plasma species with the ramie fibers on the plane electrode for the first time.